THE IMPORTANCE OF TEACHING MUSIC THEORY IN MUSIC EDUCATION (ResearchJet Journal of Analysis and Inventions, 2023)
The article shows the importance of music education in the educational process for students studying in the specialty "Elementary Music Theory", as well as the specifics of the industry's professional activities through the theme of the musical system. Information is given about the features of musical sounds, their significance in creating an artistic image.